Determination of Cnidilin and Its Two Metabolites in Rat Plasma by High-performance Liquid Chromatography-Electrospray Ionization Tandem Mass Spectrometry - Zhu, Hong; Liu, Pengwei; Shi, Xiaowei; Xu, Huijun; Ren, Yanping; Wang, Qiao; Zhang, Lantong (Planta Medica, 2013)
Simple, fast, and sensitive HPLC coupled with an electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) method for the simultaneous determination of cnidilin and its two metabolites, 3″,8-methoxy-isoimperatorin (M1) and 5″-hydroxyl-8-methoxy-isoimperatorin (M2), in rat plasma has been developed. Pimpinellin was used as the internal standard and the total analysis time was 7 min. Methanol was the only reagent during the process of sample handling used as a protein precipitant. The analytes were separated on a reversed-phase C18 column with gradient elution consisting of 0.5 ‰ aqueous formic acid and methanol (containing 0.5 ‰ formic acid) in the multiple-reaction monitoring mode. Cnidilin, M1, M2, and the internal standard could be well ionized under positive electrospray ionization conditions. Full validation of the method (linearity, precision, accuracy, limit of detection, and limit of quantification) was carried out and the method was successfully employed in a metabolism study of cnidilin administered to rats at a dose of 24 mg/kg. The pharmacokinetic parameters of cnidilin determined after orally administrating the single coumarin to the rat were obtained and the mass fragmentation pathways for analysis are proposed in this article.
Keywords: cnidilin; HPLC-ESI-MS; metabolites; pharmacokinetics; Radix Angelicae Dahuricae